EVALUASI TATA KELOLA SAMPAH DI KABUPATEN KENDAL DALAM PERSPEKTIF GOOD ENVIRONMENTAL GOVERNANCE DAN AGENDA TRANSISI HIJAU NASIONAL - Maulida Putri Rahmawati (Yayasan Nusantara Hasana Berdikari, 2026)
Waste management represents an increasingly complex environmental governance challenge, requiring an approach that goes beyond mere waste handling to include reduction at the source and support for the national green transition agenda. This study aims to evaluate waste management through the lens of Good Environmental Governance (GEG) and analyze its alignment with the national green transition agenda, focusing on the context of Kendal Regency. A Systematic Literature Review (SLR) was conducted on scholarly literature from the past five years regarding waste management, GEG, public participation, institutional aspects, collaboration, the circular economy, and environmental sustainability. The synthesis identifies six key aspects determining the quality of waste management: regulation and law enforcement; public participation; transparency and accountability; institutional capacity and collaboration; management effectiveness; and orientation toward the circular economy and green transition. The findings indicate that Kendal Regency’s primary challenge lies in low rates of waste reduction at the source, resulting in a management system that remains largely focused on waste handling. The study concludes that strengthening GEG—through governance that is participatory, transparent, accountable, collaborative, and circular-economy-oriented—is essential to drive the transformation of waste management in Kendal Regency toward a more ecological and sustainable system.